An Assessment of Quality of Life in Patients With Asthma Through Physical, Emotional, Social, and Occupational Aspects. A Cross-Sectional Study - Zelal Kharaba; Zelal Kharaba; Emilie Feghali; Farah El Husseini; Hala Sacre; Carla Abou Selwan; Sylvia Saadeh; Sylvia Saadeh; Souheil Hallit; Souheil Hallit; Souheil Hallit; Feras Jirjees; et al. (Frontiers Media S.A., 2022)
BackgroundAsthma is a prevalent hyperactive airway disease with physical and emotional impact. Severe asthma is associated with considerable health-related quality of life (HRQoL). The aim of this study is to assess the quality of life through physical, emotional, social and occupational aspects and evaluate the factors affecting HRQoL in patients with asthma.MethodsThis is a cross-sectional multicenter study conducted on adult asthmatic patients enrolled from community pharmacies across different Lebanese geographic areas.ResultsHaving wheezing sometimes and most of the time (Beta = −0.144 and −0.552), experiencing anxiety sometimes and most of the time (Beta = −0.205 and −0.573), encountering sleep problems sometimes and most of the time (Beta = −0.270 and −0.553), having previous chest discomfort sometimes and most of the time (Beta = −0.421 and −0.713), and having depression most of the times (Beta = −0.415) were associated with higher lower quality of life scores. On the other side, holding a secondary level of education was associated with a higher quality of life score (Beta = 0.192).ConclusionThis study highlights that asthma affects adults' quality of life through social, emotional, physical, and occupational impacts. Improved follow-up and patient education may be essential in the future to stop disease progression and achieve ideal therapeutic outcomes.